CALIDAD DE ATENCIÓN DEL PROFESIONAL DE SALUD RADIOLÓGICO EN LOS SERVICIOS DE RADIOLOGÍA Y TOMOGRAFÍA ORAL PERCIBIDA POR ESTUDIANTES DE LA CLÍNICA ODONTOLÓGICA, UNSLG, 2016 - DURAND DIEZ, FRANCISCO (2016)
Objective: Determine the quality of care of the radiological health professional in radiology services compared to oral tomography services perceived by students of the dental clinic, UNSLG 2016. Methodology: Observational, comparative, prospective, cross-sectional study. Made up of 436 students who are in the fifth year of the Faculty of Dentistry at the Dental Clinic, and attend the Oral Radiology and Oral Tomography services during the period between 2016. Frequencies and percentages were used. To determine the perceived quality of care in the two services, the chi square test (x2) was used, p <0.05. Results: The quality of care of the radiological health professional in the oral radiology services was regular compared to the oral tomography service, which was good, with significant differences (p = 0.000). The quality of care, according to the technical dimension. scientist, the radiological health professional of the oral radiology service was regular and in the oral tomography service it was good. The quality of care, according to the interpersonal dimension, of the radiological health professional in the oral radiology service was regular and in the oral tomography service it was good. The quality of care, according to the environmental dimension, of the radiological health professional in the oral radiology service was poor and in the oral tomography service it was good. Conclusion: There is a better perception of the quality of care in the oral tomography service than in the oral radiology service (p = 0.000) Key words: Perception of care, radiological health professional, oral radiology, oral tomography.